TINGKAT MOTIVASI SISWA KELAS IX DALAM PEMBELAJARAN PENDIDIKAN JASMANI DI SMPN 1 SIAK HULU - Hari Oktaria Asyar; Sasmarianto (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The aim of this research is to see the level of student learning motivation in physical education learning in class IX students at SMPN 1 Siak Hulu. Based on the results of observations of class IX students at SMPN 1 Siak Hulu, several causes of students' lack of motivation in participating in physical education learning include many students being lazy in participating in physical education learning at school, the lack of attractive presentation of physical education learning activities by teachers at school, lack of Facilities and infrastructure in schools can also cause a lack of student motivation because they cannot be optimal in carrying out physical education learning activities, as well as students being less active in physical education learning. Therefore, teachers must be able to provide interesting learning and also be able to modify facilities and infrastructure so that learning can be optimal so that it can increase student motivation. The test used in this research used a questionnaire or questionnaire with a Likert scale. The sample in this study was 72 class IX students at SMPN 1 Siak Hulu. From the results found in the field regarding the level of learning motivation of class IX students at SMPN 1 Siak Hulu, the results were classified as